Kajian tinjauan kesediaan guru-guru sejarah menerapkan kemahiran pemikiran sejarah kepada para pelajar - Zahara Aziz,; Nik Azleena Nik Ismail, (penerbit ukm, 2007)
The article reports on the readiness of history teachers in Dungun District to inculcate historical thinking skills among students. This study focused on five aspects which included 1) procedural knowledge; 2) pedagogical knowledge; 3) the use of audio-visual aids (AVA); 4) management of learning activities; 5) the attitude of history teachers themselves. Questionnaires were distributed to 114 history teachers in fifteen secondary schools in Dungun District. The results showed that the teacher’s readiness with regards to those five aspects mentioned above were moderate as a whole. However, among those five aspects, the attitude aspect, showed a very positive indication. The findings also suggested that there was a significant difference between teachers who were trained to teach History and those who were not. Similarly, the finding also suggested the teachers who attended related courses were more prepared than those who did not attend any course. For the use of audio-visual aids (AVA) and management of learning activities aspects, the result showed that teachers with ten years of teaching experience were more prepared. In contrast, the findings did not show any significant difference in the aspects of procedural knowledge and pedagogical knowledge compared to their teaching history experiences.